2013
DOI: 10.1007/s10450-013-9481-z
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of ordered mesoporous materials sorption properties towards amino acids

Abstract: The adsorption of amino acids such as L-phenylalanine and L-histidine was carried out on a series of mesoporous carbons obtained with the use ordered silicas KIT-6, SBA-16, SBA-15 as templates and furfuryl alcohol as carbon precursor. Small angle XRD analysis confirmed the ordered mesoporous structures of all materials obtained. They were also characterised by well-developed surface areas and high pore volumes. Adsorption behaviour of amino acids on ordered mesoporous carbons was investigated in potassium phos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 17 publications
1
7
0
1
Order By: Relevance
“…Additionally, these adsorbents need a long contact time with the adsorbate [18][19][20][21][22]. Therefore, with a high specific surface area, large pore volume, suitable pore size (2-50 nm), high degree of surface reactivity and effective adsorption quality, activated carbon has become the most desirable adsorbent [23][24][25][26].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Additionally, these adsorbents need a long contact time with the adsorbate [18][19][20][21][22]. Therefore, with a high specific surface area, large pore volume, suitable pore size (2-50 nm), high degree of surface reactivity and effective adsorption quality, activated carbon has become the most desirable adsorbent [23][24][25][26].…”
Section: Ftir Analysismentioning
confidence: 99%
“…Recently much attention has been paid to the ordered mesoporous carbons (pore size range from 2 to 50 nm) possessing unique physical and chemical properties, such as high surface area, large pore volume, specific chemical properties and good mechanical stability [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Another scientific group has investigated the sorption behaviour of five selected amino acids such as glutamic acid, arginine, phenylalanine, leucine, and alanine on mesoporous materials (SBA-15, Al-SBA-15, CH 3 (10 %)-SBA-15, and CH 3 (20 %)-SBA-15) . We have found that L-histidine has been so far adsorbed on mesoporous carbon CMK-3 (Vinu et al 2006) and C SBA-16 and C SBA-15 (Goscianska et al 2013c). Up to date, there have been a few publications concerning the potential application of modified ordered mesoporous silica for L-histidine adsorption.…”
Section: ?mentioning
confidence: 98%